The effectiveness of a marketing virtual reality learning simulation : A quantitative survey with psychophysiological measures - Sung, Billy; Mergelsberg, Enrique; Teah, Min; D’Silva, Brandon; Phau, Ian (British journal of educational technology, 2021)
Virtual reality (VR) technology has been shown to be a promising teaching method in STEM subjects. Extending these findings, the current study is the first to develop and examine the feasibility of using a VR simulation in marketing (ie, a non-STEM subject). Specifically, the levels of immersion and three learning outcomes (learning attitude, enjoyment and performance) were compared between the marketing students who learned the same content through a VR simulation prototype versus a traditional static video presentation. Learning enjoyment was measured using facial electromyography, which served as a more objective measures for the feeling of enjoyment. Compared to the video condition, the results showed that VR resulted in a higher experience of immersion, learning attitude and learning enjoyment. Furthermore, immersion was found to fully mediate the positive effects of the VR simulation on learning attitude, but not enjoyment. Surprisingly, students in the video condition performed better on the knowledge-based test than those in the VR condition. The current study suggests that the current prototype of the VR simulations should be used as supplementary resource to increase the learning attitude and enjoyment, but not as a main teaching material to enhance knowledge-based performance in the marketing discipline. [Author abstract]